2013
DOI: 10.1080/14681811.2012.760447
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond homonormativity in teacher training: experiences from South Australia

Abstract: As growing numbers of lesbian mother families enter the Australian education system, there comes with this an injunction to better include such families. The first step in such inclusion is to ensure that teachers are provided with knowledge about lesbian mother families that moves beyond simply refuting stereotypes, and toward acknowledgement of the specific experiences and needs of this family form. At the same time, however, it is important that educators, when attempting to include lesbian mothers and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Teacher training programs should ensure that teachers are provided with knowledge about lesbian and gay families that moves beyond simply refuting stereotypes, and toward acknowledgment of specific experiences and needs of various forms of families, including lesbian mothers and gay fathers (Riggs & Due, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Teacher training programs should ensure that teachers are provided with knowledge about lesbian and gay families that moves beyond simply refuting stereotypes, and toward acknowledgment of specific experiences and needs of various forms of families, including lesbian mothers and gay fathers (Riggs & Due, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite LGBTIQ parents’ accounts of insensitivity and stigma in ECEC settings (Cloughessy & Waniganayake, 2017; Cloughessy et al, 2017; Goldberg, 2014; Goldberg & Smith, 2014a), and EC educators’ self-reported need for training and resources on working with LGBTIQ-parented families (Beren, 2013; Church et al, 2018), limited research has focussed on the provision of pre- or in-service teacher training on meeting the needs of LGBTIQ-parented families (see, for example, Beren, 2013; Janmohamed, 2014; Riggs & Due, 2013). Somewhat counter-intuitively, it appears that even when EC educators hold positive attitudes towards LGBTIQ-parented families, they are less likely to act upon their stated attitudes (Hedge, Averett, White, & Deese, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although this topic may be addressed in some initial teacher education courses (Hedge et al, 2014; Riggs & Due, 2013), it is suggested that addressing this across all initial teacher education courses is important.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This link between better contextual knowledge and SRE teaching is not just asking how we can include the concerns of a somewhat excluded minority in school-based SRE, but is about integrating these findings into current debates about what should be taught in SRE to everyone (Haggis and Mulholland, 2014;Riggs and Due, 2013). Research of this kind will expand the scope of this discussion by answering the call for knowledge about young people's lived experience of relationships and sexuality for the purposes of SRE.…”
Section: Introductionmentioning
confidence: 99%